Physicochemical properties of nanostructured lipid carriers as colloidal carrier system stabilized with polysorbate 20 and polysorbate 80 - How, Chee Wun; Abdullah, Rasedee; Abbasalipourkabirreh, Roghayeh (Academic Journals, 2011)
Nanostructured lipid carriers (NLC), a colloidal carrier system offer many advantages as drug carrier. Incorporation of liquid lipid can improve the loading capacity of drugs in the NLCs. The NLC20 and NLC80 were produced by high-pressure homogenization technique, stabilized with polysorbate 20 and polysorbate 80, respectively. Transmission electron microscopy showed that these NLCs were spherical. Photon correlation spectroscopy showed that the average size of NLC80 and NLC20 were 102.8 ± 0.1 and 261.63 ± 8.56 nm, respectively, and their zeta potentials were -23.93 ± 0.75 and -30.57 ± 0.06 mV, respectively. The results suggest that NLC80 is a more stable formulation. X-ray diffractometry and differential scanning calorimetry showed that NCLs were less crystalline than the bulk lipid. The melting point depression of NLC80 was 5.71°C below bulk lipid’s melting point (61.56°C), while NLC20 exhibited two melting points at 54.80 and 59.10°C. These findings suggest that polysorbate 80 was a better dispersing agent for NLC than polysorbate 20. The physicochemistry properties of the NLCs are greatly influenced by the type of surfactant used. The small size and superior particle surface to volume ratio would increase loading efficiency and bioavailability of drugs, thus making NLC a promising drug delivery system.